ENGELBERT KAEMPFER’S MAP AS A NEW SOURCE ON EARLY RUSSIAN FISHING SETTLEMENTS (UCHUGS) IN THE VOLGA DELTA IN THE LATE 17TH CENTURY: INTERPRETATION OF TERMS - Koten'kov, Sergej Anatol'evic; Lobaceva, Dar'a Maksimovna (History, Archeology and Ethnography of the Caucasus, 2025)
This study aims to identify toponyms denoting uchugs – the earliest Russian fishing settlements established in the Volga Delta during the 17th century – on Engelbert Kaempfer’s map of 1697 and to conduct a comparative-historical analysis using other cartographic sources. Specific objectives include translating and identifying the toponyms on Kaempfer’s map; comparing them with those appearing on Adam Olearius’s maps (1647), seventeenth- and nineteenth-century drawings of Russian uchugs, and modern place names; and determining the precise locations and ownership of these uchugs. Detailed analysis of Engelbert Kaempfer’s map demonstrates that it is a unique seventeenth-century cartographic source. It complements existing knowledge of the socio-economic development of the Volga Delta, accurately reflects the geographical configuration of the Caspian lowland in that period, and illustrates European interest in the region’s resources. Toponyms designating fisheries in the delta portion of the map have been identified, and their correspondence to the names of the rivers or channels on which the uchugs were located has been established. The primary reason for the abandonment of uchugs was the rise in Caspian Sea level during the eighteenth and nineteenth centuries, which flooded settlements and altered hydrological conditions. The results broaden our understanding of historical cartography, the economic history of fishing in the region, and its cultural geography.